2014
DOI: 10.14411/eje.2014.021
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry and biosynthesis of insect pigments

Abstract: abstract. The functional role and commercial importance of insect pigments have been studied for well over a century. They are classified into those synthesized by insects, which include anthraquinones, aphins, pterins, tetrapyrroles, ommochromes, melanins and papiliochromes, and those sequestered from their host plants, the antioxidative carotenoids and water-soluble flavonoids. They can also be categorized into those that are produced by cyclization of linear precursors, e.g. anthraquinones, aphins and tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 113 publications
1
122
0
1
Order By: Relevance
“…The biosynthesis pathway and annotation details are given in Additional file 2: Figure S2 and Additional file 1: Sheet 16. Carotene and xanthophyll, together constituting carotenoid pigments, are lipid soluble, containing no nitrogen and absorb light with green and blue wavelengths, which is producing a green, blue-green, blue and red colour to the insect integument and haemolymph [54]. Carotenoids play an important role in antioxidation, photoreception and colouration [50, 54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biosynthesis pathway and annotation details are given in Additional file 2: Figure S2 and Additional file 1: Sheet 16. Carotene and xanthophyll, together constituting carotenoid pigments, are lipid soluble, containing no nitrogen and absorb light with green and blue wavelengths, which is producing a green, blue-green, blue and red colour to the insect integument and haemolymph [54]. Carotenoids play an important role in antioxidation, photoreception and colouration [50, 54].…”
Section: Resultsmentioning
confidence: 99%
“…Carotene and xanthophyll, together constituting carotenoid pigments, are lipid soluble, containing no nitrogen and absorb light with green and blue wavelengths, which is producing a green, blue-green, blue and red colour to the insect integument and haemolymph [54]. Carotenoids play an important role in antioxidation, photoreception and colouration [50, 54]. However, none of the genes in this pathway were uniformly differentially expressed between the sexes.…”
Section: Resultsmentioning
confidence: 99%
“…S1) than 3OH-kynurenine and cannot be detected by Raman, but have been successfully detected by SERS (Smyth et al, 2011). Pterins are abundant in insects (Shamim et al, 2014), and a previous genomic study suggested that pterins could be synthesized de novo in spiders (Croucher et al, 2013). Therefore, pterins could also be responsible for the colour production of these yellow setae.…”
Section: Discussionmentioning
confidence: 99%
“…Insect body color is primarily attributed to the existence of pigment molecules in the cuticle or underlying epidermis, which include anthraquinones, aphins, pterins, tetrapyrroles, ommochromes, melanins, carotenoids and flavonoids . Among these compounds, pterins, melanins and carotenoids are involved in the formation of black, yellow, red, orange pigments .…”
Section: Resultsmentioning
confidence: 99%